2015
DOI: 10.1016/j.nbd.2014.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes and microglia but not neurons preferentially generate N-terminally truncated Aβ peptides

Abstract: The neuropathological hallmarks of Alzheimer's disease include extracellular neuritic plaques and neurofibrillary tangles. The neuritic plaques contain β-amyloid peptides (Aβ peptides) as the major proteinaceous constituent and are surrounded by activated microglia and astrocytes as well as dystrophic neurites. N-terminally truncated forms of Aβ peptides are highly prevalent in neuritic plaques, including Aβ 3-x beginning at Glu eventually modified to pyroglutamate (Aβ N3pE-x), Aβ 2-x, Aβ 4-x, and Aβ 5-x. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 74 publications
6
51
0
Order By: Relevance
“…However, the astrocyte clearance function can also be compromised in AD (Mulder et al, 2012), and a significant increase in secreted Ab might occur in this pathological situation. However, the small changes detected in Ab40/ 42 could be because astrocytes are able to produce and secrete different patterns of N-terminally truncated Ab variants that were no detected in this study (Oberstein et al, 2014). Finally, it is possible that in the present model, cholesterol promoted the interaction between BACE-1 and APP without affecting the activity of g-secretase to complete the Ab production.…”
Section: Discussionmentioning
confidence: 59%
“…However, the astrocyte clearance function can also be compromised in AD (Mulder et al, 2012), and a significant increase in secreted Ab might occur in this pathological situation. However, the small changes detected in Ab40/ 42 could be because astrocytes are able to produce and secrete different patterns of N-terminally truncated Ab variants that were no detected in this study (Oberstein et al, 2014). Finally, it is possible that in the present model, cholesterol promoted the interaction between BACE-1 and APP without affecting the activity of g-secretase to complete the Ab production.…”
Section: Discussionmentioning
confidence: 59%
“…Six years ago, we reported that treatment of SH‐SY5Y cells overexpressing wild type human APP with membrane‐anchored tripartite BACE1 inhibitors reduced the overall cellular generation of Aβ peptide, but at the same time led to a relative increase in specific Aβ peptide variants displaying isoelectric points (pI) different from that of known Aβ peptides starting with Asp(1), that is, pI of approximately 5.4 according to 2D‐Western blot analysis . Mass spectrometry data indicated that the BACE1‐inhibitor‐resistant Aβ peptides comprise primarily N‐truncated peptides starting with Arg(5), and have a pI of approximately 6.5 according to a novel capillary isoelectric‐focusing (CIEF) immunoassay . In addition, a minor fraction of BACE1‐inhibitor‐resistant Aβ peptides with a pI of approximately 6.0 was observed in supernatants of APP overexpressing SH‐SY5Y cells (see Figure 2 in ref.…”
Section: Resultsmentioning
confidence: 99%
“…[32] Mass spectrometry data indicated that the BACE1-inhibitor-resistant Ab peptides comprise primarily N-truncated peptides starting with Arg(5), and have ap Io fa pproximately 6.5 according to an ovel capillary isoelectric-focusing (CIEF) immunoassay. [16,18,[33][34][35] In addition, am inor fraction of BACE1-inhibitor-resistant Ab peptides with ap Io fa pproximately 6.0 was observed in supernatants of APP overexpressing SH-SY5Yc ells (see Figure 2i nr ef. [18]).…”
Section: Resultsmentioning
confidence: 99%
“…The fly genome contains one APP-related gene, APP-like (APPL), which, when mutated, causes defects in neuronal outgrowth, synaptic stability, and behavior, and Appl mutant flies have provided important insight into endogenous APP signaling mechanisms in the CNS (46). Across all model organisms, an overwhelming number of studies have explored the role of neuronal APP, but relatively little is known about the function of glial APP, despite the fact that APP is also expressed in mammalian oligodendrocytes, astrocytes, and microglia (21, 47). A recent study explored how glial APPL influences sleep-wake cycles in adult flies.…”
Section: Glia-neuron Signaling and Implications For Neurodegenerativementioning
confidence: 99%